2016
DOI: 10.7314/apjcp.2015.16.18.8625
|View full text |Cite
|
Sign up to set email alerts
|

Could Tumor Size Be A Predictor for Papillary Thyroid Microcarcinoma: a Retrospective Cohort Study

Abstract: Background: Central lymph node metastasis(CLNM) is common in papillary thyroid microcarcinoma (PTMC). The aim of this study was to define the pathohistologic risk grading based on surgical outcomes. Materials and Methods: Statistical analysis was performed to figure out the optimal cut-off values of size in preoperative ultrasound images for defining the risk of CLNM in papillary thyroid microcarcinoma. Receiver operating characteristic curves (ROC) studies were carried out to determine the cutoff value(s) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…Although PTMC is considered an indolent cancer with relatively benign biologic behavior and an excellent prognosis, certain aspects of PTMC biologic behavior are quite poor, which may present as lymph node metastasis, distant metastasis, recurrence, and may even cause death. 22 24 As the reported mortality rate of PTMC ranges from 0% to 1% and presents relatively benign biologic behavior, 8 some researchers reported that PTMC should not be overtreated. Rather, periodic observation without surgical treatment 1 has been suggested, and in the American Thyroid Association and the British Thyroid Association guidelines, lobectomy was described as the primary operative management of PTMC without aggressive features, for example, extrathyroidal extension, multifocality, and central or lateral lymph node metastasis; 25 , 26 moreover, prophylactic central lymph node dissection was not recommended without a suspicious enlarged lymph node in the treatment of PTC 27 because it provides no survival benefit 28 and may even increase the incidence of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PTMC is considered an indolent cancer with relatively benign biologic behavior and an excellent prognosis, certain aspects of PTMC biologic behavior are quite poor, which may present as lymph node metastasis, distant metastasis, recurrence, and may even cause death. 22 24 As the reported mortality rate of PTMC ranges from 0% to 1% and presents relatively benign biologic behavior, 8 some researchers reported that PTMC should not be overtreated. Rather, periodic observation without surgical treatment 1 has been suggested, and in the American Thyroid Association and the British Thyroid Association guidelines, lobectomy was described as the primary operative management of PTMC without aggressive features, for example, extrathyroidal extension, multifocality, and central or lateral lymph node metastasis; 25 , 26 moreover, prophylactic central lymph node dissection was not recommended without a suspicious enlarged lymph node in the treatment of PTC 27 because it provides no survival benefit 28 and may even increase the incidence of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, investigators have attempted to identify the tumor diameter cut-off value predictive of aggressiveness by ROC curves in PTMC (tumor size ≤10 mm) and have proposed a further subdivision of PTMC by cut-off point related to lymph node metastasis to guide management of these minute lesions. 8 , 9 This proposal has had highly variable results, with some studies reporting that tumors ≤5 mm are less likely to metastasize, while other studies have reported a cut-off of 6, 7, or 8 mm. 37 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that US features may be also useful in predicting the biological behaviors of PTC. As the tumor size on ultrasound images is the most available preoperative parameter, someone reported 26 that the maximum diameter of tumor was associated with a significantly increased risk of cervical LNM. Our results was in accord with this opinion, and the optimal cut-off value of tumor size obtained based on the ROC curve was 0.95 cm (AUC = 0.72).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al claim that the size of PTMC in ultrasound images are helpful to predict the aggressiveness of the tumors, it may become an easy predictor for PTMC prognosis and assist us to choose treatment (Wang et al, 2015) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%